2021
DOI: 10.3390/su13063349
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Perspectives of Pakistan and Turkey: Current Analysis and Policy Recommendations

Abstract: To a great extent, Pakistan and Turkey rely on imported fossil fuels to meet their energy demands. Pakistan is moving in the right direction, placing focus on renewable energy resources in its current infrastructure in order to address the energy shortage. Several projects (e.g., wind power and solar PV (photovoltaic) technologies) are operational or under development; they are intended to reduce energy challenges in Pakistan. The new government in Pakistan aims to increase the share of renewable energy in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Even in today's contemporary world, developed and developing nations consume conventional fuels for energy, transportation and industrial sectors, which are the biggest drivers of global climate change. 19,143 According to World Health Organization (WHO), carbon footprint and air pollution are the two most significant contributors to worldwide health concerns. Air pollution and carbon footprints have a negative impact on health and the number of fatalities caused by excessive temperatures, storms and catastrophic events.…”
Section: Opportunities For Renewable Energy In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in today's contemporary world, developed and developing nations consume conventional fuels for energy, transportation and industrial sectors, which are the biggest drivers of global climate change. 19,143 According to World Health Organization (WHO), carbon footprint and air pollution are the two most significant contributors to worldwide health concerns. Air pollution and carbon footprints have a negative impact on health and the number of fatalities caused by excessive temperatures, storms and catastrophic events.…”
Section: Opportunities For Renewable Energy In Pakistanmentioning
confidence: 99%
“…The fundamental purpose of this policy is to improve energy security, financial advantages, preservation of natural resources, long-term development and economic equality by employing locally accessible resources, which will be strengthened under the National Energy Act of 2019. 19,22 Aside from large-scale renewable projects, small sustainable energy projects for lighting, pumping systems and power generation, are also promoted.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, the main focus should be on job creation and financial development, focusing on environmental impacts, shifting consumer attention to renewable energy for society, and improving smart belt systems effectively and efficiently. Renewable energy sources are the best option to minimize pollution, and increase the economy, energy security, employment opportunities, and poverty by reducing the dependence of poor people on natural resources [150,151].…”
Section: Adverse Impact Of Renewable Energy Projects On the Environmentmentioning
confidence: 99%
“…According to Rosso-Cerón and Kafarov (2015), social acceptance defines people's positive and negative attitudes toward various green energy resources and technologies. In Pakistan, various studies have been conducted on renewable energy sources and renewable energy technologies (Bhutto et al, 2011;Bhutto et al, 2013;Kamran, 2018;Zafar et al, 2018;Ali et al, 2019;Kashif et al, 2020;Bhutto et al, 2021;Uddin et al, 2021), but no study has been reported on public perception about RE sources, technology, and WTP.…”
Section: Introductionmentioning
confidence: 99%